2008
DOI: 10.2147/tcrm.s2527
|View full text |Cite
|
Sign up to set email alerts
|

Treating oligohydramnios with extract of Salvia miltiorrhiza: A randomized control trial

Abstract: Objective: To determine whether purifi ed herbal extract of Salvia miltiorrhiza can improve the amniotic fl uid volume in pre-term oligohydramnios by improving uteroplacental circulation. Methods: Forty-three pregnant women with oligohydramnios received a daily intravenous dose of 30 mL of salvia extract mixed with 5% glucose 500 mL. A control group of 41 women received daily 5% glucose 500 mL only. The amniotic fl uid index (AFI) was assessed at least twice a week by ultrasonographists who were blinded to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…As a traditional Chinese medicine, it has been to treat oligohydramnios for decades. Chu et al (9) identified that Danshen extract was an effective medicine to increase the amniotic fluid volume in pre-term patients suffering oligohydramnios, and the absolute (increased fluid) effective rate of Danshen extract was approximately 70%. But the molecular pathway responsible for the beneficial effects of Danshen extract on oligohydramnios has not been elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a traditional Chinese medicine, it has been to treat oligohydramnios for decades. Chu et al (9) identified that Danshen extract was an effective medicine to increase the amniotic fluid volume in pre-term patients suffering oligohydramnios, and the absolute (increased fluid) effective rate of Danshen extract was approximately 70%. But the molecular pathway responsible for the beneficial effects of Danshen extract on oligohydramnios has not been elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Wenwen Zhang 1 , Yiwen Zhang 1 , Xiaoli Hu 1 , Huihui Cheng 1 , Ying Hua 1 , Xueqiong Zhu 1 (9). Although efficacy of Danshen extract therapy for oligohydramnios has been proven in clinical research, only effective for some patients and the molecular mechanisms responsible for the beneficial effects of Danshen extract on oligohydramnios remain poorly understood.…”
Section: Danshen Extract Regulates the Expression Of Aquaporin 3 In Hmentioning
confidence: 99%
“…The therapeutic effects on oligohydramnios were speculated to include improvement in the placentalblood circulation and control of membrane permeability at the placenta. 14) So it was speculated that some types of herbal medicines have been effective for the treatment of oligohydramnios.…”
Section: Discussionmentioning
confidence: 99%
“…Purified herbal extract of Salvia miltiorrhiza also useful to treat oligohydramnios but daily infusion of 500 ml, 14) the ambulatory-treatment isn't easy to manage, although is low degree, have same risk as maternal hydration therapy. 13) On the other hand the risk of Gorei-San treatment is low.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple pharmacological activities of S. miltiorrhiza have been identified, including antioxidant and anti-inflammatory activities, and the extract is used to treat miscarriage, edema, and platelet aggregation (15)(16)(17)(18). In recent years, clinical research has confirmed that S. miltiorrhiza effectively improves AFV in oligohydramnios, with approximately 70% cases were found AFV increased (19). In a previous study, we demonstrated that S. miltiorrhiza extract increased AQP3 protein levels in human primary culture amnion epithelium cells (hAECs) obtained from normal AFV and from patients with isolated oligohydramnios (20).…”
Section: Inmentioning
confidence: 99%